Pemanfaatan Ular Tangga Edukatif untuk Menurunkan Stres dan Meningkatkan Kadar Hb Remaja - Khairunnisa Batubara; Afrizal Hasan; Shandra; Wiyanna Mathofani Siregar; Naila Khalis; Salsa Billa; M. Hafinawa Husaini (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2026)
Teenagers are particularly susceptible to psychological stress, which can affect physiological problems like low hemoglobin (Hb) levels. Adolescents who experience unmanaged stress may experience worsening health and a higher risk of anemia. The purpose of this community service project is to evaluate how well instructional snakes and ladders media may lower stress levels and raise hemoglobin levels in teenagers. Thirty teenagers aged 15-17 years were subjected to an educational-participatory approach using a pretest-posttest strategy. For four weeks, the intervention was implemented using a modified version of the snakes and ladders game that included resources on stress reduction, healthy eating, and preventing anemia. An adolescent stress scale questionnaire was used to gauge stress levels, and a digital hemoglobinometer was used to assess hemoglobin levels both before and after the intervention. The activity's findings demonstrated that adolescents' average stress scores significantly decreased following the intervention, while their average hemoglobin levels increased. Teenagers' active involvement in the game also improved their comprehension of stress management and the significance of iron consumption. The instructional snakes and ladders medium has been shown to be a creative, entertaining, and successful method for promoting teenagers' physical and mental well-being.